Treatment of hepatitis C genotype 1 infection in Germany: effectiveness and safety of antiviral treatment in a real-world setting - Höner zu Siederdissen, Christoph; Buggisch, Peter; Böker, Klaus; Schott, Eckart; Klinker, Hartwig; Pathil-Warth, Anita; Pfeiffer-Vornkahl, Heike; Berg, Thomas; Sarrazin, Christoph; Hüppe, Dietrich; Manns, Michael P.; Mauss, Stefan (United european gastroenterology journal, 2018)
Background: In pivotal studies with direct-acting antivirals (DAAs), rates of sustained virological response in hepatitis C genotype 1 infection are >90%. - Objective: The objective of this article is to assess real-world safety and effectiveness of DAA treatment in a prospective multicenter registry study. - Methods: The German Hepatitis C-Registry includes 6606 patients with genotype 1 from 246 centers, treated between February 2014 and June 2016 at the discretion of the physician. - Results: A total of 4846 patients completed treatment and follow-up; 51% of these patients were treatment experienced and 28% had liver cirrhosis. Comorbidities were reported in 76% of patients, including HIV co-infection in 8%. SVR12 was 92% with 91% in GT1a and 93% in GT1b. HIV co-infected patients (n = 247) had an SVR12 of 92%. Treatment was discontinued prematurely in 2.5%. In multivariate analysis, SVR12 was dependent on the choice of antiviral regimen (OR 1.33 (1.24-1.43); p < 0.001), negatively associated with presence of liver cirrhosis (OR 0.71 (0.56-0.89); p < 0.003) and positively associated with female gender (OR 1.52 (1.21-1.91); p < 0.001). - Conclusion: Data from this real-world registry show SVR12 rates close to those obtained in clinical studies. Discontinuation rates are low, confirming good tolerance of the regimens and good adherence of patients (Trial registration number DRKS00009717, German Clinical Trials Register, DRKS).
Gesehen am 01.10.2019